Partial root-zone drying irrigation and water utilization efficiency by the potato crop in semi-arid regions in China - Kaiyun X.; Xiao-Xue W.; Ruofang Z.; Xiufeng G.; Shibiao Z.; Victor, Michael; Carla G.; Adolfo P.; Roberto Q. (Elsevier, 2012)
Two field experiments were conducted in two semi-arid areas in northern China to test the response of three potato varieties to supplemental irrigation. Conventional furrow irrigation was compared to the partial root-zone drying (PRD) irrigation system at different watering levels, with and without plastic mulching. Reducing the supplementary water to one half, under both soil-climate conditions tested, did not affect fresh tuber yield; whereas water use efficiency (WUE) was equally incremented by all the reduced water treatments. When this reduction in the amount of supplementary water was managed through the PRD system, the distribution of moisture in the soil seemed to be improved and the potential evaporation was decreased due to the reduced evaporative surface exposed by PRD. The results showed that application of irrigation water per unit area can be reduced relative to common practice in Inner Mongolia and Gansu, maintaining the tuber yields currently obtained by local farmers. A further reduction in the amount of supplemental water, without a substantial decrease in yield, might be feasible with the PRD technique but this may require a more sophisticated irrigation management; and further research to estimate the cost-benefit ratio of such sophistication is needed. Results also showed that under low precipitation and low water retention capacity, the use of plastic mulching and a potato variety selected for drought-prone environments can make the difference for maintaining a high yield while reducing the wasteful use of the water resources.